A Study on Regression Co-efficient between the Factor Gender and Attitude towards Search Engine Marketing in Kanyakumari district (International Journal of Food and Nutritional Sciences, 2022)
Search Engine Marketing (SEM) is a form of Internet marketing that involves the promotion of websites by increasing their visibility in search engine results pages primarily through paid advertising. SEM is also called essential word marketing or PPC advertising, which allows advertisers to place bids on specific keywords or phrases and have their advertisement show up alongside the organic search engine. It is also observed that almost twenty percent of advertisers are moving their advertising budgets to SEM from traditional print and other kinds of mass media. The best search engines like Google, Bing and yahoo are concentrating on maximizing traffic to a web page. In this study 400 respondents is taken for the study by convenient sampling method from the block of Kanniyakumari district. In the present study, an attempt has been made to analyze the impact of gender on the attitude towards Search Engine Marketing with the help of multiple regression analysis. The result show the regression coefficient of attitude towards Search Engine Marketing among male and female respondents. The significantly negatively influencing attitude among male respondents are entertainment factor, in formativeness and credibility, where as among female respondents are entertainment irritating and credibility. By using a combination of paid and organic search strategies, companies can attract high-quality traffic to their websites and improve their online presence.